PERSYARATAN E-COMMERCE MERUGIKAN KONSUMEN PADA TRANSAKSI BARANG ELEKTRONIK DI MARKETPLACE [E-COMMERCE REQUIREMENTS HARMING CONSUMERS IN ELECTRONIC GOODS TRANSACTIONS IN THE MARKETPLACE] - Widya Fitri Adilia (Lex Prospicit, 2023)
Issues related to consumer rights are often neglected in the era of digital technology and the laws and regulations of Law Number 8 of 1999 concerning Consumer Protection are felt to be increasingly irrelevant. Many are still found in e-commerce transactions through marketplaces, which ignore consumer rights through digital requirements made unilaterally by business actors. This writing is focused on the purchase of electronic goods by consumers in e-commerce transactions through marketplaces, so that a formulation of the problem is compiled about how the forms of e-commerce requirements are burdensome and detrimental to consumers in electronic goods transactions in the marketplace, and how are consumers' efforts to obtain rights to goods electronics purchased in the marketplace when viewed from a review of Indonesian law. The writing methodology is carried out by using empirical normative research to assist in solving problems in the field of consumer protection law and assisting in the discovery of ideas for the development of legal science in providing protection for consumer rights in the digital technology era. E-commerce requirements that are burdensome and detrimental to consumers in electronic goods transactions in the marketplace are in the form of standard clauses in which there are still many provisions that violate the contents of Article 18 Paragraph (1) of Law Number 8 of 1999 concerning Consumer Protection. Efforts by consumers to obtain rights to electronic goods purchased in the marketplace within existing regulatory provisions, that law in Indonesia still does not have specific standard requirements, and a form of supervision to take firm action against marketplace business actors who violate the provisions prohibiting the standard clauses included in the requirements e-commerce transactions.  Bahasa Indonesia Abstrak: Permasalahan terkait hak konsumen yang sering terabaikan di era teknologi digital, peraturan perundang-undangan dalam Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen dirasa sudah semakin kurang relevan. Masih banyak ditemukan dalam transaksi e-commerce melalui marketplace, yang mengabaikan hak-hak konsumen melalui persyaratan digital yang dibuat sepihak oleh pelaku usaha. Penulisan ini difokuskan pada pembelian barang elektronik oleh konsumen dalam transasksi e-commerce melalui marketplace, sehingga disusun sebuah rumusan masalah tentang bagaimanakah bentuk persyaratan e-commerce yang memberatkan dan merugikan konsumen pada transaksi barang elektronik di marketplace, serta bagaimana upaya konsumen untuk mendapatkan hak atas barang elektronik yang dibeli di marketplace bila dilihat dari tinjauan hukum Indonesia. Metodologi penulisan dilakukan dengan menggunakan jenis penelitian normatif empiris guna membantu dalam memecahan persoalan di bidang hukum perlindungan konsumen dan membantu penemuan gagasan pengembangan ilmu hukum dalam memberikan perlindungan hak konsumen di era teknologi digital. Persyaratan e-commerce yang memberatkan dan merugikan konsumen pada transaksi barang elektronik di marketplace ialah berupa klausula baku yang isinya masih banyak ditemukan ketentuan yang melanggar isi Pasal 18 Ayat (1) Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Upaya konsumen untuk mendapatkan hak atas barang elektronik yang dibeli di marketplace dalam ketentuan regulasi yang ada, bahwa hukum di Indonesia masih belum memiliki standar persyaratan khusus, dan bentuk pengawasan untuk menindak tegas para pelaku usaha marketplace yang melanggar ketentuan larangan klausula baku yang dicantumkan di dalam persyaratan transaksi e-commerce.